Social epistemology - Haddock, Adrian; Millar, Alan, Ph. D.; Pritchard, Duncan (Oxford : Oxford University Press, 2010)
Recent epistemology has reflected a growing interest in the social dimension of the subject. This volume presents new work by leading philosophers on a wide range of topics in social epistemology, such as the nature of testimony, the epistemology of disagreement, and the social genealogy of the concept of knowledge.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Social epistemology